On the relationships between circulation types and changes in rainfall variability in Greece - Maheras, P.a; Tolika, K.a; Anagnostopoulou, C.a; Vafiadis, M.b; Patrikas, I.b; Flocas, H.c (International Journal of Climatology, 2004)
An attempt is made to examine rainfall variability over the Greek area in relation to 500 hPa atmospheric circulation. Daily precipitation series from 22 evenly distributed Greek stations have been used for the period 1958-2000, along with the classification scheme of daily circulation types at 500 hPa for the same period. The seasonal frequency and the trends of circulation types have been calculated. It was found that there is a general positive trend of anticyclonic circulation types and a negative one for cyclonic types. The seasonal trends of rainy days and the precipitation totals have also been calculated and analysed. A general decreasing tendency of winter rainfall is observed; the decreasing trend during autumn and spring is less significant. Concerning the frequency and intensity of rainfall per circulation type, a decreasing tendency becomes evident for the majority of the stations during winter, whereas there is an increasing tendency during autumn. A multiple regression-cross-validation model was developed using the seasonal frequency of circulation types as predictors and the seasonal rainfall totals as predictants. Only the winter modelled precipitation shows a good agreement with the observed precipitation, whereas for the other seasons the agreement is relatively poor. This could be caused by the influence of different factors that are not captured by the classification scheme used. The proposed model could serve as a circulation-based downscaling method that could be further applied to geopotential data available from general circulation models in order to study regional climatological consequences of future climate scenarios. Copyright © 2004 Royal Meteorological Society.
Keywords: Anticyclonic circulation; atmospheric circulation; Circulation models; Climatology; Earth atmosphere; Eastern Hemisphere; environmental impact; Eurasia; Europe; Greece; Natural frequencies; Precipitation (chemical); precipitation (climatology); rain; rainfall; Regression Analysis; Southern Europe; trend analysis; World